GENDER DIFFERENCES IN PERCEPTIONS OF GOOD AND EFFECTIVE ENGLISH TEACHER - Udayana, I Made; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study aims to investigate how male and female view the meaning of a good and effective English teacher. The study was conducted in SMA Negeri 1 Banjar and carried out using a descriptive qualitative research method with open ended questionnaire as an instrument distributed to 83 students. The data were collected through open ended questionnaire by providing 10 statements regarding the characteristics of good English teacher and 10 statements for effective English teachers. Male students consider the teacher-student relationship more important, or more precisely, a relaxed and calm state due to a good relationship between teacher and student in declaring a good English teacher, while female students consider the instructional competencies of teachers more important in declaring a good English teacher. Then regarding the opinions of male and female students about the most important character to declare an effective English teacher, they choose different characters, but both refer to the teacher's pedagogical ability, especially in understanding students' abilities and characteristics, because if they already have good abilities in understanding character and student abilities, the impact will also be very good on student learning outcomes.